Composite foil as well as preparation method and processing equipment thereof
By forming a conductive layer on the surface of the foil, thinning and pre-drying the edges, and then applying insulating glue to form an insulating layer, the internal short circuit problem caused by thermal shrinkage of the separator at high temperatures is solved, and the safety performance of the battery is improved. Production efficiency.
Patent Information
- Application Number
- CN202411666584.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The thermal shrinkage of the separator of lithium-ion batteries at high temperatures causes direct contact between the positive and negative electrode active material layers, causing short circuits in the battery, reducing safety performance.
After coating the conductive paste on the surface of the foil to form a conductive layer, edge thinning and pre-drying are performed, followed by coating insulating glue on the edge of the conductive layer to form an insulating layer, and the conductive layer and insulation are avoided by controlling the drying temperature and time. The problem of the layer melting.
It effectively avoids the risk of internal short circuit caused by thermal shrinkage of the diaphragm at high temperatures, improves the safety performance of the battery, and improves the quality and production efficiency of composite foils.
Smart Images

Figure CN119495751A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a composite foil material and a preparation method and processing equipment thereof. Background Art
[0002] As lithium-ion batteries are increasingly used in electric vehicles and grid energy storage, their safety performance has received increasing attention. At present, the safety performance of lithium-ion batteries has become one of the important factors limiting the rapid development of lithium-ion batteries. Lithium-ion batteries may experience thermal shrinkage of the diaphragm under high temperature conditions, and the width of the overhang area of the diaphragm over the positive and negative electrodes becomes smaller or even negative, resulting in direct contact between the positive and negative active material layers, causing a short circuit in the battery, and thus reducing the safety performance of lithium-ion batteries. Summary of the invention
[0003] In order to solve the problem of internal short circuit of the battery caused by thermal shrinkage of the diaphragm at high temperature and improve the safety performance of the battery, the present invention provides a composite foil material and a preparation method and processing equipment thereof.
[0004] According to a first aspect of the present invention, there is provided a method for preparing a composite foil, comprising the following steps:
[0005] S1. Coating a conductive paste on at least one surface of the foil to form a conductive layer;
[0006] S2. The edge of the conductive layer is thinned, and the conductive layer is pre-dried for the first time along the width direction of the conductive layer to obtain a semi-finished product;
[0007] S3. An insulating slurry is coated on the edge of the conductive layer of the semi-finished product to form an insulating layer, and after a second drying, a composite foil is obtained;
[0008] The temperature of the first pre-drying is T1 and the time is t1, and the temperature of the second drying is T2 and the time is t2. T1, T2, t1, and t2 satisfy: T1 = (0.8-1.2) × T2, and t1 = (0.01-0.5) × t2.
[0009] The existing technology improves the safety performance of the battery by coating insulating glue on the edges of the positive and negative active material layers to reduce the risk of short circuit in the battery caused by direct contact between the positive and negative active material layers due to thermal shrinkage of the battery diaphragm at high temperatures, thereby improving the safety performance of the battery.
[0010] In order to simplify the electrode processing technology, the present invention advances the insulating glue processing flow to the foil processing, that is, insulating glue is applied in advance to the edge of the carbon-coated layer (i.e., the conductive layer) of the carbon-coated aluminum foil to form an insulating layer. At the same time, in order to improve production efficiency, the carbon-coated layer and the insulating glue of the carbon-coated foil are baked at one time after coating. However, this will cause the carbon-coated slurry and the insulating glue slurry to fuse with each other at the contact position before drying, resulting in unclear boundary line between the two, making it impossible for the die-cutting system to identify the edge grip when the electrode is subsequently cut into the pole ears, resulting in miscutting, affecting the production yield.
[0011] In the preparation method of the composite foil provided by the present invention, first, after a conductive layer is formed by coating a conductive paste on the surface of the foil, the edge of the conductive layer is first thinned to thin the edge of the conductive layer, that is, the amount of paste per unit area of the edge of the conductive layer is reduced, and then the conductive layer on the surface of the foil is pre-dried along the width direction of the conductive layer (i.e., the first pre-drying). Since the surface density of the paste after the thinning of the edge of the conductive layer is lower, the paste at the edge of the conductive layer can be more easily dried. At this time, the thinned area of the edge of the conductive layer has been completely dried. Then, an insulating glue is coated on the edge of the conductive layer to form an insulating layer. Even if the conductive layer and the insulating layer are in contact and overlap, after drying again (i.e., the second drying), the conductive layer and the insulating layer will not have a melting problem. In addition, the area of the edge of the conductive layer that has not been thinned has not reached a completely dry state, and the solid content of the conductive layer from the edge to the middle after the first pre-drying gradually decreases, which reduces the preparation process of the composite foil. First, the stress difference between the conductive layer and the insulating layer during the pre-drying process can effectively avoid the problem that the conductive layer is prone to cracking during the second drying; second, compared with heating the edge of the conductive layer alone, the first pre-drying is mainly aimed at the thinned area of the conductive layer, which can ensure uniform heating over the width of the foil, ensure that the foil is heated uniformly in the width direction, make the internal stress of the conductive layer more uniform, avoid heating the edge of the conductive layer alone, resulting in uneven internal stress of the conductive layer, curling of the edge of the composite foil and cracks in the conductive layer, and improve the quality of the composite foil; third, by regulating the temperature and time of the first pre-drying and the second pre-drying and controlling them within the above range, the thinned area of the conductive layer can be pre-dried, which not only avoids the problem of melting during the drying process after the insulating slurry is applied to the conductive layer, but also does not affect the flatness of the insulating slurry when it is applied to the conductive layer, and the time of the first pre-drying is short, which improves the production efficiency of the composite foil. Through the combined effect of the above three aspects, the problem of short circuit in the battery caused by direct contact between the positive and negative active material layers due to thermal shrinkage of the battery diaphragm at high temperature can be solved, and the problem of melting of the conductive layer and the insulating layer and the generation of stress difference in the preparation process of the composite foil can be solved. The quality and production efficiency of the composite foil are also guaranteed. At the same time, there is no need to design an empty foil area between the conductive layer and the insulating layer, which further guarantees the function of the insulating layer, reduces the risk of internal short circuit in the battery using the composite foil provided by the present invention, and improves the safety performance of the battery.
[0012] Preferably, T1 = (0.9-1.0) × T2.
[0013] Preferably, T2 = 80-110°C.
[0014] Preferably, t1 = (0.04-0.2) × t2.
[0015] Preferably, t2 = 0.05-0.15 min.
[0016] By optimizing the temperature and time of the first pre-drying, the production efficiency of the composite foil can be further improved while further improving the melting problem of the conductive layer and the insulating layer during the drying process.
[0017] If the temperature of the first pre-drying is too high, the edge of the conductive layer cannot be cooled in time and the temperature is too high, resulting in the insulating slurry being dried and shaped before it is leveled when applied to the edge of the conductive layer, affecting the coating flatness of the formed insulating layer. If the temperature of the first pre-drying is too low, the thinned area of the conductive layer will not be completely dried. When the insulating slurry is applied to the edge of the conductive layer, there will still be a risk of melting between the conductive layer and the insulating layer. If the first pre-drying time is too long, the temperature of the edge of the conductive layer will be too high, and the first pre-drying process will be too long, reducing the production efficiency of the composite foil.
[0018] Preferably, the conductive paste contains conductive carbon black.
[0019] Preferably, the insulating paste contains boehmite.
[0020] Preferably, in S3, the process of coating the insulating adhesive on the edge of the conductive layer of the semi-finished product to form the insulating layer also includes thinning the insulating layer near the edge of the conductive layer.
[0021] According to a second aspect of the present invention, a composite foil is provided, comprising a foil and a conductive layer and an insulating layer arranged on the surface of the foil, wherein the conductive layer comprises a first main region and a first thinned region, wherein the thickness of the first thinned region is less than the thickness of the first main region, and the first thinned region overlaps with an edge portion of the insulating layer.
[0022] In the composite foil provided by the present solution, the first thinned area in the composite conductive layer on the surface of the foil overlaps with the edge portion of the insulating layer, so that the conductive layer and the insulating layer in the finally formed composite foil can be distinguished, and the boundary line between the conductive layer and the insulating layer is clear, so that the electrode sheet of the composite foil using the present solution can be accurately identified by the die-cutting system when the electrode ear is subsequently cut, thereby avoiding miscutting and improving the production yield.
[0023] Preferably, the insulating layer comprises a second main region and a second thinned region, the thickness of the second main region is smaller than the thickness of the second thinned region, and the first thinned region partially overlaps with the second thinned region.
[0024] Preferably, the thickness of the first thinned region decreases along a direction from close to the first main region to away from the first main region, and / or the thickness of the second thinned region decreases along a direction from close to the second main region to away from the second main region.
[0025] The above-mentioned arrangement is conducive to achieving a natural transition between the thinned area and the main area of the conductive layer and the insulating layer in the composite foil, thereby avoiding the situation where the ridges are unable to completely cover the insulating layer due to the generation of ridges at the boundaries between the thinned area of the conductive layer and the main area, or the generation of ridges at the boundaries between the conductive layer and the thinned area of the insulating layer and the main area, resulting in the conductive layer and the insulating layer being difficult to fit well together, thereby affecting the flatness of the active material layer in the electrode sheet using the composite foil during the coating process and the performance of the electrode sheet.
[0026] Preferably, the width of the first thinned area is 1 to 10 mm, and / or the width of the second thinned area is 0.5 to 8 mm.
[0027] Preferably, the width of the second thinned area is A, the width of the insulating layer is B, and A and B satisfy 0.05≤A / B≤0.5.
[0028] By controlling the width of the first thinned area of the conductive layer and the second thinned area of the insulating layer within the above range, it is helpful to ensure the overall flatness of the composite foil, improve the flatness of the active material layer in the electrode using the composite foil during the coating process and the performance of the electrode.
[0029] If the width of the first thinned area of the conductive layer is too wide, it will affect the overall flatness of the composite foil; if the width of the first thinned area of the conductive layer is too narrow, the boundary line with the insulating layer is likely to be unclear, affecting the production yield of the composite foil.
[0030] If the width of the second thinned area of the insulating layer is too wide, it will make it difficult for the insulating layer to fit stably with the conductive layer, thereby affecting the performance of the composite foil; if the width of the second thinned area of the insulating layer is too narrow, when overlapping with the first thinned area of the conductive layer, it may easily cause the thickness of the overlapping area to be too thick, thereby affecting the performance of the composite foil.
[0031] According to a third aspect of the present invention, there is provided a composite foil processing equipment, which includes a conductive layer coating device, an insulating layer coating device, a first pre-drying device and a second drying device; the conductive layer coating device includes a conductive slurry coating roller, the insulating layer coating device includes an insulating adhesive slurry coating roller, and the projections of the conductive slurry coating roller and the insulating adhesive slurry coating roller at least partially overlap; the conductive slurry coating roller includes a main coating area and a thinning coating area which are continuously arranged, and the depth of the main coating area is greater than the depth of the thinning coating area.
[0032] Preferably, the conductive paste coating roller is a gravure roller.
[0033] Preferably, the insulating slurry coating roller is a transfer coating roller.
[0034] Preferably, the insulating adhesive coating roller comprises a flat coating area.
[0035] Preferably, the insulating adhesive coating roller further comprises a thinning area, and the bottom surface of the thinning area protrudes from the flat coating area. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a schematic structural diagram of the composite foil provided by the present invention.
[0037] The reference numerals in the drawings are: 1 foil, 2 conductive layer, 2-1 first main region, 2-2 first thinned region, 3 insulating layer, 3-1 second main region, 3-2 second thinned region.
[0038] Figure 2 This is a process flow chart for preparing the composite foil provided by the present invention. DETAILED DESCRIPTION
[0039] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] A composite foil material having a structure as follows Figure 1 As shown, the composite foil comprises a foil 1 and a conductive layer 2 and an insulating layer 3 arranged on the surface of the foil 1, wherein the conductive layer 2 comprises a first main body region 2-1 and a first thinned region 2-2, the thickness of the first thinned region 2-2 is less than the thickness of the first main body region 2-1, and the thickness of the first thinned region 2-2 gradually decreases along the direction from close to the first main body region 2-1 to far away from the first main body region 2-1, the insulating layer 3 comprises a second main body region 3-1 and a second thinned region 3-2, the thickness of the second main body region 3-1 is less than the thickness of the second thinned region 3-2, and the thickness of the second thinned region 3-2 gradually decreases along the direction from close to the second main body region 3-1 to far away from the second main body region 3-2, and the first thinned region 2-2 overlaps with the second thinned region 3-2;
[0042] The composite foil of this embodiment adopts the composite foil processing equipment and refers to Figure 2The composite foil is prepared according to the process flow chart shown in the figure, wherein the composite foil processing equipment used includes a conductive layer coating device, an insulating layer coating device, a first pre-drying device and a second drying device; the conductive layer coating device includes a conductive slurry coating roller, the insulating layer coating device includes an insulating adhesive slurry coating roller, and the projections of the conductive slurry coating roller and the insulating adhesive slurry coating roller at least partially overlap; the conductive slurry coating roller includes a main coating area and a thinning coating area which are continuously arranged, and the depth of the main coating area is greater than the depth of the thinning coating area.
[0043] In the above composite foil processing equipment, the conductive slurry coating roller is a gravure roller, and the insulating slurry coating roller is a transfer coating roller; the insulating slurry coating roller includes a flat coating area and may also include a thinning area, and the bottom surface of the thinning area protrudes from the flat coating area.
[0044] The preparation process of the composite foil provided in this embodiment is as follows Figure 2 As shown, it is prepared by the following steps:
[0045] S1. A foil material 1 (blank foil) having a length of 12 μm and a width of 800 mm is placed in a composite foil processing device, and a conductive paste containing carbon black is coated on both surfaces of the foil material 1 using a gravure coating roller (conductive paste coating device) having a groove width of 680 mm to form a conductive layer 2;
[0046] The gravure coating roller includes a flat coating area with a width of 660 mm and thinning areas with a width of 10 mm on both sides of the flat coating area. The groove depth of the flat coating area is 2 μm.
[0047] S2. The edge of the conductive layer 2 is thinned to divide the conductive layer into a first main area 2-1 and a first thinned area. In the process of coating the conductive slurry with a gravure coating roller, the flat coating area of the gravure coating roller can make the conductive layer form the first main area 2-1, and the thinning areas on both sides of the gravure coating roller can make the edge of the conductive layer form the first thinned area 2-2. The conductive layer is subjected to a first pre-drying process by a heating roller (first pre-drying device) with an effective heating length of 0.5 m to obtain a semi-finished product.
[0048] S3. The insulating slurry containing boehmite is coated on the first thinned area of the conductive layer of the semi-finished product by a transfer coating roller (insulating slurry coating device) to form an insulating layer, and then dried for a second time in a long oven (second drying device) having a length of 5 m to obtain a composite foil;
[0049] The first pre-drying temperature T1 and the second drying temperature T2 are both 90°C, T1 = 1.0 × T2;
[0050] The transfer coating roller is provided with coating areas which are in parallel contact with the projection of the gravure coating roller, and are respectively arranged on both sides of the projection of the groove of the gravure coating roller, and the coating width on both sides is 8mm, and the coating surface of the coating area is parallel to the foil;
[0051] The foil passes through the conductive slurry coating device, the first pre-drying device, the insulating adhesive slurry coating device, and the second drying device at a uniform speed of 90m / min.
[0052] The time for the first pre-drying and the second drying is the effective heating length of the foil divided by the foil conveying speed. The time for the first pre-drying t1 = the effective heating length of the heating roller 0.5m / the foil conveying speed 90m / min = 0.00556min, and the time for the second drying t2 = the long oven length 5m / the foil conveying speed 90m / min = 0.0556min, t1 = 0.1×t2.
[0053] Example 2
[0054] This embodiment provides a composite foil material, and compared with the embodiment 1, the difference in structure is that the coating surface of the coating area of the transfer coating roller is an inclined surface, and the side close to the conductive layer protrudes more than the side away from the conductive layer, and the angle with the foil material is 1°, and the coating area on the transfer coating roller overlaps with the projection of the gravure coating roller, and the single-side overlap width is 5mm. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0055] Example 3
[0056] This embodiment provides a composite foil material, and compared with the embodiment 1, the difference in structure is: the first pre-drying device is a short oven with a length of 2m, and the temperature T1 of the first pre-drying and the temperature T2 of the second drying are both 80°C, the foil material running speed is 100m / min, the first pre-drying time t1 = effective heating length of the short oven 2m / foil material running speed 100m / min = 0.02min, T1 = T2, t1 = 0.36×t2. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0057] Example 4
[0058] This embodiment provides a composite foil material, and compared with the embodiment 1, the difference in structure is: the first pre-drying device is a heating roller with an actual heating length of 0.1m, the heating temperature of the first pre-drying is 110℃, and the time of the first pre-drying is t1=the effective heating length of the heating roller 0.1m / the foil material running speed 90m / min=0.0011min; the second drying device is a long oven with a length of 10m, the heating temperature of the second drying is 90℃, and the time of the second drying is t2=the length of the long oven 10m / the foil material running speed 90m / min=0.1111min; T1=1.22T1, t1=0.0099t2. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0059] Example 5
[0060] This embodiment provides a composite foil material, and compared with the embodiment 1, the difference in structure is: the temperature of the first pre-drying T1 = 130°C, the temperature of the second drying T2 = 110°C, T1 = 1.18 × T2. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0061] Example 6
[0062] This embodiment provides a composite foil material, and compared with the embodiment 1, the difference in structure is: the temperature of the first pre-drying T1 = 60°C, the temperature of the second drying T2 = 75°C, T1 = 0.8 × T2. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0063] Example 7
[0064] This embodiment provides a composite foil material, and compared with the embodiment 1, the difference in structure is that the first pre-drying device is a heating roller with an actual heating length of 1.3m, the first pre-drying time t1 = effective heating length of the heating roller 1.3m / foil material running speed 90m / min = 0.0144min, t1 = 0.26×t2. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0065] Example 8
[0066] This embodiment provides a composite foil material, and compared with the embodiment 1, the difference in structure is that the first pre-drying device is a heating roller with an actual heating length of 1.3m, the first pre-drying time t1 = the effective heating length of the heating roller 0.15m / the foil material running speed 90m / min = 0.0017min, t1 = 0.031×t2. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0067] Comparative Example 1
[0068] This comparative example provides a composite foil material, and compared with Example 1, the difference in structure is that the gravure coating roller (conductive slurry coating device) is not provided with a thinning zone, that is, the conductive layer of the composite foil material is not provided with a first thinning zone, and the first pre-drying treatment is not performed. Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0069] Comparative Example 2
[0070] This comparative example provides a composite foil material, which is different from Example 1 in that the gravure coating roller (conductive slurry coating device) is not provided with a thinning zone, that is, the conductive layer of the composite foil material is not provided with a first thinning zone, but the conductive layer is subjected to a first pre-drying treatment, and the coating zones of the gravure coating roller and the transfer coating roller are spaced apart, and the spacing on both sides is 3 mm. Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0071] Comparative Example 3
[0072] This comparative example provides a composite foil material, and compared with Example 1, the difference in structure is that in the preparation step S2 of the composite foil material, after the edge of the conductive layer is thinned, the first pre-drying treatment is not performed. Except for the above difference, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0073] Comparative Example 4
[0074] This comparative example provides a composite foil material, and compared with Example 1, the difference in structure is that the gravure coating roller (conductive slurry coating device) is not provided with a thinning zone, that is, the conductive layer of the composite foil material is not provided with a first thinning zone, and only the edge area of the conductive layer is subjected to the first pre-drying treatment, and the main area is not subjected to the first pre-drying treatment. Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0075] Test Case
[0076] 1. Participants
[0077] In this test example, the composite foils prepared in Examples 1 to 8 and Comparative Examples 1 to 4 were used as test objects, the composite foils were applied to the preparation of batteries, and relevant performance tests were performed on the batteries.
[0078] Prepare the battery as follows:
[0079] (1) Preparation of positive electrode
[0080] The ternary cathode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, binder polyvinylidene fluoride (PVDF), and conductive agent carbon black (SP) are mixed in a mass ratio of 97:1.6:1.4, added into solvent N-methylpyrrolidone (NMP), mixed evenly, and a positive electrode slurry with a solid content of 45% is obtained. The positive electrode slurry is coated on both surfaces of a composite foil (the empty foil is aluminum foil) to form a positive electrode active material. After vacuum drying, a positive electrode sheet is obtained.
[0081] (2) Preparation of negative electrode
[0082] The negative electrode active material silicon carbon material (silicon mass fraction is 10%), the aqueous binder polyacrylic acid (PAA), and the conductive agent carbon nanotubes are mixed in a mass ratio of 96:3:1, added into the solvent deionized water, mixed evenly, and a negative electrode slurry with a solid content of 45% is prepared. The negative electrode slurry is coated on both surfaces of a negative electrode current collector copper foil with a thickness of 12 μm to form a negative electrode active coating. After vacuum drying, a negative electrode sheet is prepared.
[0083] (3) Preparation of diaphragm
[0084] A polyethylene (PE) film having a ceramic layer on its surface is used as the diaphragm, and the heat shrinkage temperature of the diaphragm is 130°C.
[0085] (4) Preparation of electrolyte
[0086] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1M.
[0087] (5) Battery assembly
[0088] The positive electrode sheet, separator and negative electrode sheet are stacked in order, the separator is placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell, the bare battery cell is placed in an aluminum-plastic film of an outer packaging shell, and the electrolyte is injected after drying, and a battery is obtained through vacuum packaging, standing, forming, shaping and other processes, wherein the edge of the negative electrode active coating exceeds the edge of the positive electrode active coating by 2 mm, and the separator exceeds the negative electrode active coating by 5 mm.
[0089] 2. Test content
[0090] (1) Heat resistance test
[0091] At 25°C, an internal resistance ACR test was performed on the battery using an AC internal resistance tester, and the internal resistance of the battery was measured to be a1. The battery was then placed in a heating box at a constant temperature of 135°C for 30 minutes, taken out, and cooled to room temperature. The internal resistance ACR test was performed on the battery again using an AC internal resistance tester, and the internal resistance of the battery was measured to be a2. The ACR reduction of the battery was calculated according to the following formula: ACR reduction (%) = (a1-a2) / a1×100%.
[0092] (2) Capacity test
[0093] At room temperature (25°C), the battery was placed for 12 hours, charged to 4.2V at a constant current rate of 0.1C, with a cut-off current of 0.05C, and placed for 10 minutes. The battery was then discharged at a constant current rate of 0.3C with a cut-off voltage of 2.5V, and the discharge capacity of the battery was recorded.
[0094] 3. Experimental results
[0095] Table 1 Battery related performance test
[0096] Group a1(mΩ) a2(mΩ) ACR reduction (%) Capacity(mA) Example 1 6.4 6.5 -1.6 1885 Example 2 6.9 6.7 2.9 1871 Example 3 6.3 6.0 4.8 1877 Example 4 6.2 6.5 -4.8 1853 Example 5 6.4 5.8 9.4 1860 Example 6 6.8 6.5 2.9 1838 Example 7 6.4 6.2 4.7 1862 Example 8 6.3 6.7 -4.8 1849 Comparative Example 1 6.3 6.2 1.6 1703 Comparative Example 2 6.8 4.9 27.9 1875 Comparative Example 3 6.3 6.2 1.6 1750 Comparative Example 4 / / / /
[0097] The relevant performance test results of the batteries using the composite foils prepared in Examples 1 to 8 and Comparative Examples 1 to 4 are shown in Table 1.
[0098] In the preparation process of the composite foil provided in Examples 1 to 8, after a conductive layer is formed by coating a conductive paste on the surface of the foil, the edge of the conductive layer is first thinned to make the edge portion of the conductive layer thinner, that is, the amount of paste per unit area at the edge portion of the conductive layer is reduced, and then the foil is pre-dried (i.e., the first pre-drying) to dry the paste at the edge portion of the conductive layer. At this time, the edge of the conductive layer is already dry, and then insulating glue is coated on the edge of the conductive layer to form an insulating layer. Even if the conductive layer and the insulating layer are in contact and overlap, after drying again (i.e., secondary drying), the conductive layer and the insulating layer will not have a melting problem, and the boundary between the conductive layer and the insulating layer is clear. The composite foils prepared in Examples 1 to 8 are applied to pole pieces and batteries. The boundary between the conductive layer and the insulating layer is clear, so that the die-cutting system can better identify the grasping edge when the pole piece is subsequently cut into pole ears. The actual effective area of the pole piece is controllable, so that the battery has a higher discharge capacity at 25°C and the ACR reduction of the battery is low, indicating that the battery has good heat resistance, reducing the risk of internal short circuit when the battery has thermal abnormalities, so that the battery has good safety performance in actual application.
[0099] During the preparation process of the composite foil provided in Example 2, the insulating layer is also thinned, and the insulating layer covers the thinned area of part of the conductive layer. This can not only reduce the risk of empty foil gaps between the insulating layer and the conductive layer due to equipment errors and reduce the risk of short circuits in the battery, but also improve the flatness of the foil after rolling, and reduce the risk of wrinkling during the rolling process due to the large difference in thickness between the conductive layer and the insulating layer.
[0100] Compared with Example 1, the length and time of the first pre-drying of the composite foil provided in Example 3 during the preparation process are longer, resulting in a higher temperature of the conductive layer and incomplete cooling. At this time, coating the insulating slurry on the edge of the conductive layer will cause the insulating slurry to dry and form before it is leveled, resulting in poor flatness of the formed insulating layer. Moreover, due to the long first pre-drying time, its production efficiency is lower than that of Example 1.
[0101] Compared with Example 1, the length of the heating roller and the drying time of the first pre-drying of the composite foil provided in Example 4 during the preparation process are shorter, and the conductive layer and the insulating adhesive still have partial melting problems, and the melting width is 0.5-1 mm.
[0102] Compared with Example 1, the first pre-drying temperature T1 and the second drying temperature T2 of the composite foil provided in Examples 5 to 6 during the preparation process do not satisfy the two relationship equations T1 = (0.9 to 1.0) × T2 and / or T2 = 80 to 110°C, and the first pre-drying temperature used in the preparation process of the composite foil in Example 5 is too high, and the temperature of the foil is too high when it reaches the insulating glue coating process, resulting in poor leveling of the insulating glue, uneven coating, and local foil leakage. After the heat resistance test, it was found that the internal resistance was reduced, indicating that there may be an internal short circuit, and the first pre-drying temperature used in the preparation process of the composite foil in Example 6 is too low, the thinning area is not completely dried, and there may be a risk of melting, but compared with no pre-drying, the boundary between the conductive layer and the insulating glue is relatively clear, and the effect on the edge grip of the die cutting is small. The test results show that the ACR reduction of Examples 5 to 6 is higher than that of Example 1, and the capacity of the battery is lower than that of Example 1.
[0103] Compared with Example 1, the first pre-drying time t1 and the second drying time t2 of the composite foil provided in Examples 7 to 8 during the preparation process do not satisfy the two relationship equations t1 = (0.04 to 0.2) × t2 and / or t2 = 0.05 to 0.15 min. The test results show that the ACR reductions of Examples 7 to 8 are higher than those of Example 1, and the battery capacities are lower than those of Example 1.
[0104] Compared with Example 1, the gravure coating roller (conductive slurry coating device) in the processing equipment used in the preparation process of the composite foil provided in Comparative Example 1 is not provided with a thinning zone, and the conductive layer and the insulating layer will have serious melting problems during the drying process. The melting width is 4 to 6 mm, which seriously affects the positioning and gripping in the subsequent die-cutting process. The actual effective area of the electrode is uncontrollable, which may ultimately lead to a low capacity of the battery.
[0105] Compared with Example 1, the gravure coating roller (conductive slurry coating device) in the processing equipment used in the preparation process of the composite foil provided in Comparative Example 2 is not provided with a thinning area, and the coating areas of the gravure coating roller and the transfer coating roller are spaced apart, with a spacing of 3 mm on both sides, resulting in the final composite foil exposing a relatively large amount of empty foil area. The battery using the composite foil of Comparative Example 2 is prone to internal short circuit in the event of thermal anomalies, which is specifically manifested in that the ACR reduction is significantly higher than that in Example 1, which significantly reduces the safety performance of the battery.
[0106] Compared with Example 1, the gravure coating roller (conductive slurry coating device) used in the preparation process of the composite foil provided in Comparative Example 4 does not have a thinning zone, that is, the conductive layer of the composite foil does not have a first thinning zone, and only the edge area of the conductive layer is subjected to the first pre-drying treatment, and the main area does not undergo the first pre-drying treatment. The surface of the conductive layer of the composite foil provided in Comparative Example 4 cracks at the preheating boundaries on both sides, and the foil is discarded and cannot be used to make electrodes and batteries.
[0107] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A method for preparing a composite foil, characterized in that: The following steps are involved: S1. Coating a conductive paste on at least one surface of the foil to form a conductive layer; S2. The edge of the conductive layer is thinned, and the conductive layer is pre-dried for the first time along the width direction of the conductive layer to obtain a semi-finished product; S3. An insulating adhesive is applied to the edge of the conductive layer of the semi-finished product to form an insulating layer, and after a second drying, the composite foil is obtained; The temperature of the first pre-drying is T1 and the time is t1, and the temperature of the second drying is T2 and the time is t2. T1, T2, t1 and t2 satisfy: T1 = (0.8-1.2) × T2, t1 = (0.01-0.5) × t2.
2. The method for preparing the composite foil according to claim 1, characterized in that: T1 = (0.9-1.0) x T2, and / or, T2 = 80-110°C.
3. The method for preparing the composite foil according to claim 1, characterized in that: t1 = (0.04 ~ 0.2) × t2, and / or, t2 = 0.05 ~ 0.15min.
4. The method for preparing the composite foil according to claim 1, characterized in that: The conductive paste contains conductive carbon black, and / or the insulating paste contains boehmite.
5. A composite foil, characterized in that: The composite foil comprises a foil and a conductive layer and an insulating layer arranged on the surface of the foil, the conductive layer comprises a first main area and a first thinned area, the thickness of the first thinned area is less than the thickness of the first main area, and the first thinned area overlaps with the edge portion of the insulating layer.
6. The composite foil according to claim 5, characterized in that: The insulating layer includes a second main body region and a second thinned region, the second main body region has a thickness smaller than that of the second thinned region, and the first thinned region partially overlaps with the second thinned region.
7. The composite foil according to claim 6, characterized in that: The thickness of the first thinned area decreases along a direction from close to the first main area to away from the first main area. and / or, The thickness of the second thinned region decreases along a direction from approaching the second main body region to away from the second main body region.
8. The composite foil according to claim 6, characterized in that: The width of the first thinned area is 1 to 10 mm, and / or the width of the second thinned area is 0.5 to 8 mm.
9. The composite foil material according to claim 6, characterized in that: The width of the second thinned area is A, and the width of the insulating layer is B. A and B satisfy 0.05≤A / B≤0.
5.
10. A composite foil processing device, characterized in that: It includes a conductive layer coating device, an insulating layer coating device, a first pre-drying device and a second drying device; The conductive layer coating device comprises a conductive paste coating roller, and the insulating layer coating device comprises an insulating adhesive paste coating roller, wherein the conductive paste coating roller and the insulating adhesive paste coating roller have projections that at least partially overlap; The conductive paste coating roller comprises a main coating area and a skived coating area which are continuously arranged, and the depth of the main coating area is greater than the depth of the skived coating area; Preferably, the conductive slurry coating roller is a gravure roller, and / or the insulating adhesive slurry coating roller is a transfer coating roller; Preferably, the insulating adhesive coating roller includes a flat coating area; Preferably, the insulating adhesive coating roller further comprises a thinning area, and the bottom surface of the thinning area protrudes from the flat coating area.
Citation Information
Patent Citations
Positive electrode for lithium ion secondary battery, positive electrode sheet for lithium ion secondary battery, and manufacturing method thereof
CN113748535A
Pole piece preparation method of composite foil current collector, pole piece and soft package battery
CN114171718A
Method for evaluating insulation of covering part
CN115280547A
Safe battery cell pole piece structure and lithium ion battery
CN115911398A
Electrode plate, preparation method of electrode plate, electrochemical energy storage device and application of electrochemical energy storage device
CN116072810A